Cloud & Crowd: New Challenges for Labour in the Digital Society - Andreas Boes; Tobias Kämpf; Thomas Lühr; Barbara Langes; Alexander Ziegler (tripleC: Communication, Capitalism & Critique, 2017)
Cloudworking and crowdsourcing are currently often seen as the epitome of a “revolution in the world of work” (Dettmer and Dohmen 2012). The paper deals with these developments and their relevance for work and society. The emergence of a global “information space” (Baukrowitz and Boes 1996) enables companies to expand the scope of their value production far beyond their formal boundaries, integrating forms of work that have been non-capitalist in character up to now. The result is a new stage of capitalist “Landnahme”. The novelty of such colonization strategies in the information space is that they endeavour to make work within and without the formal boundaries of the company mutually exchangeable, on the basis of informatized and industrialized production structures, and to capitalize on this interplay between inside and outside. This development entails great challenges in society. The social system of labour undergoes a reconstitution process which infringes on the foundations of our present labour regulation system, both upon the society and the company level.